#TITLE_ALTERNATIVE# - MUCHAMAD BAYU SAKTI PRATAMA (NIM : 13604022); Pembimbing: Dr. Romie O. Bura; Ir. Novarius Gayus, R.
Aircraft Ice Shedding is an event where ice that accumulated on an aircraft surface sheds, if the ice particle size is significant, then it can cause damage when it hits aircraft components. Ice Shedding event on aircraft is one of the FOD (Foreign Object Damage) that can endanger the safety of aircraft operation. Therefore Ice Shedding analysis needs to be done for prevention and damage reduction (if this event is inevitable.) Ice Shedding analysis consists of : shape and size predictions of ice that accumulated on aircraft surface (on wing surface for this case,) ice particle shape and size prediction, ice particle aerodynamic characteristics calculation, flowfield calculation around ice particle trajectory,and ice particle trajectory calculation and analysis. In this research, shape and size predictions of ice that accumulated on aircraft surface was done using TRAJICE software, ice particle shape and size prediction was done based on TRAJICE calculations result and from literature review, ice particle aerodynamic characteristics was predicted using CFD (Computational Fluid Dynamics), flowfield calculation around ice particle trajectory was assumed to be uniform flow, and then for ice particle trajectory calculation, it was done by programming using Fortran language. Case study was done for Indonesian Aerospace CN235-100 aircraft on holding condition for 45 minutes. Regulations that based the requirements for ice shedding case analysis and were used for this research are FAR/JAR25 ( Ã‚Â§ 25.1419), Advisory Circular (AC) 25.1419-1A, AMJ 25.1419, and Acceptable Means of Compliance and Interpretations (ACJ) 25.1419.